Effects of external magnetic field on the micro-structure of diamond-like carbon film prepared by pulsed laser deposition. (16th October 2019) - Lu, Yimin; Cheng, Yong; Huang, Guojun; Xi, Lin; Wang, Sai; Wei, Shangfang; Mi, Chaowei
Abstract: The DLC film was deposited by pulsed laser deposition in an external magnetic field, and its optical property, surface morphology and atomic bonds were researched. The simulated flight tracks of the carbon ions in the magnetic field showed that a number of the carbon ions were constrained by the Lorentz force, fling onto the substrate and forming the DLC film. The contrast between the micro-structures of the DLC films deposited in or out the magnetic field showed that the external magnetic field changed the expansion of the laser-produced plume and confined the surface diffusion of the charged particles on the substrate, improving the content of the sp3 bonds in the DLC film.